La industria del Holocausto : reflexiones sobre la explotración del sufrimiento judío / Norma G. Finkelstein ; [traducción de María Corniero Fernández]. - Finkelstein, Norman G. (Cuestiones de antagonismo, 2014)
Recalling Holocaust hoaxers such as Jerzy Kosinski and Binjamin Wilkomirski, as well as the demagogic constructions of writers like Daniel Goldhagen, Finkelstein contends that the main danger posed to the memory of Nazism's victims comes not from the distortions of Holocaust deniers but from self-proclaimed guardians of Holocaust memory. Drawing on a wealth of untapped sources, he exposes the double shakedown of European countries as well as legitimate Jewish claimants, and concludes that the Holocaust industry has become an outright extortion racket.